# Factoring by Grouping (Part 1)

How to factor a polynomial by grouping (part 1): examples and their solutions.

## Example 1

Factor the first two terms:*a*^{2} - 2*a* = *a*(*a* - 2).

Factor the next two terms

with making the (*a* - 2) factor:

+5*a* - 10 = +5(*a* - 2).

The GCF is (*a* - 2).

So, by factoring,*a*(*a* - 2) + 5(*a* - 2) = (*a* + 5)(*a* - 2).

## Example 2

Factor the first two terms:*x*^{2} - 4*xy* = *x*(*x* - 4*y*).

Factor the next two terms

with making the (*x* - 4*y*) factor:

-3*x* + 12*y* = -3(*x* - 4*y*).

The GCF is (*x* - 4*y*).

So, by factoring,*x*(*x* - 4*y*) - 3(*x* - 4*y*) = (*x* - 3)(*x* - 4*y*).